Three-dimensional analysis of cathode ray tubes for color television - MacGregor, D.M. (IEEE transactions on electron devices, 1986)
Three-dimensional computer simulation demonstrates the principles used in the design of electron guns for color television tubes. A deformable-mesh finite difference analysis provides the electron trajectories from the cathode to the center of the screen. At the screen, the dimensions of the spot are obtained from the edge trajectory and from profiles of the current in the beam. Comparisons with measurements for three tubes show that the aspect ratios of the horizontal and vertical spot diameters agree within 14 percent or better. The computed beam currents are accurate to about 10 percent, and the optimum focus voltages to within 200 V.